Third-generation L-Lactic acid production by the microwave-assisted hydrolysis of red macroalgae Eucheuma denticulatum extract - Tong, K.T.X. (Elsevier Ltd, 2021)
The development of an efficient third-generation L-lactic acid (L-LA) production process from Eucheuma denticulatum extract (EDE) was achieved in this study. Microwave-assisted dilute acid hydrolysis (MADAH) and microwave-assisted hydrothermal hydrolysis (MAHTH) were chosen as the hydrolysis of EDE for the objective of increasing galactose yield. Single-factor optimization of hydrolysis of the EDE was studied, MADAH had high performance in galactose production relative to MAHTH, in which the yield and optimal conditions for both processes were 50.7 (0.1 M H2SO4, 120 °C for 25 min) and 47.8 (0 M H2SO4,160 °C for 35 min), respectively. For fermentation, the optimal L-LA yield was achieved at the inoculum cell density of 4 (w/w) Bacillus coagulans ATCC 7050 with 89.4 and 6 (w/w) Lactobacillus acidophilus LA-14 with 87.6. In addition, lipid-extracted Chlorella vulgaris residues (CVRs) as co-nutrient supplementation increased the relative abundance of B. coagulans ATCC 7050, thus benefiting L-LA production. © 2021 Elsevier Ltd